Review papersCurrent aspects of vitiligo genetics - Czajkowski, Rafał; Męcińska-Jundziłł, Kaja (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Vitiligo is a common acquired depigmentation disorder of the skin manifested by the presence of white macules. The disease occurs at a frequency of approximately 1–4% of the world population. Currently, the most popular theory of vitiligo development is a multifactorial hypothesis according to which genetic conditions predispose vitiligo macules to occur as a result of specific environmental factors. According to the genetic hypothesis, vitiligo inheritance is multigenic. Genetic studies conducted so far concern patients with non-segmental vitiligo. There are three basic techniques of genetic studies: candidate gene association studies, genomewide linkage studies and genome-wide association studies (GWAS). The GWAS are the “gold standard” for detecting susceptibility genes. Up to now, approximately 36 convincing non-segmental vitiligo susceptibility loci have been identified. Approximately 90% of them encode immunoregulatory proteins, while approximately 10% encode melanocyte proteins. The existence of various associations between vitiligo and other autoimmune diseases may provide new knowledge on the causes of many disorders. Examples include the inverse relationship between vitiligo and melanoma and association of vitiligo with other autoimmune diseases. The main goal of all researches is to find new, optimal therapeutic strategies for vitiligo and other autoimmune diseases.